KEWENANGAN APARAT KEPOLISIAN LALU LINTAS DALAM MELAKUKAN PENYITAAN BARANG BUKTI PELANGGARAN LALU LINTAS DI WILAYAH HUKUM POLRES PAYAKUMBUH - Ana Ramadhona (Ensiklopedia Social Review, 2021)
The exercise of authority in the form of confiscation actions carried out by members of the Payakumbuh City Police, especially traffic officers against vehicles that commit traffic violations, in taking action must be in accordance with Law Number 2 of 2002 concerning the Indonesian National Police, Law Number 22 of 2009 concerning Road Traffic and Transportation and the Criminal Procedure Code. Several inhibiting factors in confiscation of evidence in traffic include law enforcers who are often not firm in enforcing the rules, lack of facilities that support law enforcement such as the lack of traffic signs, the lack of police traffic vehicles in conducting patrols, and legal awareness that is less than adequate. There People must be able to understand traffic rules well. Regular socialization of traffic rules, firm action against traffic violators, addition of facilities and infrastructure for traffic signs can reduce traffic violations.Keywords: Authority, Police, Confiscation, Evidence, Traffic Offenders.